Environmental Degradation and Economic Growth Nexus in Liberia: Auto Regressive Distributive Lag Analysis (ARDL MODEL) - Lester Z. Tenny (International Journal of Formal Sciences: Current and Future Research Trends, 2022)
Economic growth has been said to degrade the environment. This study takes a long run analysis of the relationship between exploitation of the environment and economic performance in Liberia. The study used WDI data from 2001 to 2020 with the ARDL model in the Liberian economy. The study indicates long run analysis among population, environmental degradation, and economic growth in Liberia. Past economic performance positively affects economic growth while population of Liberia and exploitation of the environment negatively affect economic growth from the study. The study reports that population and environmental degradation were not statistically significant at 5% but the model was statistically significant with diagnostic and stability tests showing fitted good model. The study established a long run analysis. The recommendation from the study is that more environmentally friendly economic activities with huge attention on human capital development and management of the population of Liberia to optimally utilize human resources for economic development is pivotal.